2018
DOI: 10.1155/2018/6578273
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Expression of IL-32 in Diffuse and Intestinal Types of Gastric Cancer

Abstract: Introduction Gastric cancer (GC) represents one of the most common cancers worldwide, frequently diagnosed at advanced stages with poor prognosis, indicating on need for new diagnostic and prognostic markers. The aim of the study was to determine the expression of IL-32, proinflammatory and angiogenic mediators, in patients with diffuse and intestinal gastric cancer and the relationship with clinicopathological aspects. Material and Methods The tissue samples of diffuse and intestinal types of tumor of 70 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…This result was consistent with our findings that NDUFA4 was highly expressed in GC and correlated with the poor prognosis of GC patients. Gastric adenocarcinoma is histologically divided into intestinal, diffuse, mixed, and indeterminate subtypes, whereas the diffuse type of GC usually has a shorter duration of disease and poor prognosis [ 27 ]. Our results have revealed that NDUFA4 was highly expressed in all HER2-negative GC cell lines compared with normal human gastric epithelium, in which intestinal-type GC cell lines (MKN28, AGS) showed higher NDUFA4 expression in comparison to intestinal diffuse-type GC cell lines (MKN45).…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with our findings that NDUFA4 was highly expressed in GC and correlated with the poor prognosis of GC patients. Gastric adenocarcinoma is histologically divided into intestinal, diffuse, mixed, and indeterminate subtypes, whereas the diffuse type of GC usually has a shorter duration of disease and poor prognosis [ 27 ]. Our results have revealed that NDUFA4 was highly expressed in all HER2-negative GC cell lines compared with normal human gastric epithelium, in which intestinal-type GC cell lines (MKN28, AGS) showed higher NDUFA4 expression in comparison to intestinal diffuse-type GC cell lines (MKN45).…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 is mainly produced by activated T cells, NK cells, epithelial cells, and blood monocytes ( 7 ), and it has nine splice variants IL-32 α , IL-32 β , IL-32 γ , IL-32 δ , IL-32 ε , IL-32 θ , IL-32 ζ , IL-32 η , and IL-32small (IL-32sm) ( 8 , 9 ). IL-32 has been implicated in many inflammatory diseases and cancers, including rheumatoid arthritis ( 10 ), chronic obstructive pulmonary disease (COPD) ( 11 ), lymphoma ( 12 ), head and neck squamous cell carcinoma (HNSCC) ( 13 ), thyroid cancer (TC) ( 14 ), hepatocellular carcinoma (HCC) ( 15 ), lung cancer (LC) ( 16 18 ), esophageal cancer ( 19 ), gastric cancer (GC) ( 20 , 21 ), pancreatic cancer ( 22 ), colorectal cancer (CRC) ( 23 , 24 ), renal cell carcinoma (RCC) ( 25 ), breast cancer ( 26 ), and endometrial cancer (EC) ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with a more aggressive diffuse type of GC, there was a decrease in the expression of MVD in the tumor compared with GC of the intestinal type, and this decrease was associated with advanced TNM stage of the disease. There were no differences in VEGF expression in GC of diffuse and intestinal types[ 162 ].…”
Section: Results Of Angiogenesis Activity Assessment In Gcmentioning
confidence: 99%